The Role of Clusters in Knowledge Creation and Diffusion – an Institutional Perspective - Michael Steiner (European Regional Science Association (ERSA), 2004)
Clusters and networks have received renewed attention in recent years not only as a tool for regional development in general but as an institution of knowledge creation and diffusion between the knowledge infrastructure of a region and the firms within the clusters. They are therefore often regarded as geographically condensed forms of economic cooperation and knowledge exchange. The recent renaissance of interest in institutions as a factor shaping economic performance has therefore also implications for the creation and sustained existence of clusters and networks as a tool for knowledge management and as learning organisations within and across regions. This institutional perspective serves to identify additional factors influencing economic behaviour leading to cooperation. Different strands of institutional thinking –institutions as “social technologies” in the tradition of evolutionary economics, clusters as a form of Coase institution integrating positive external effects of technological knowledge, the importance of knowledge sharing in the context of the “New Institutional Economics” – emphasize that connectivity cannot be effectively coordinated by conventional markets. Clusters and networks are among the non-market devices by which firms seek to coordinate their activities with other firms and other knowledge-generating institutions. But it is also important to emphasize that clusters as coordinating institutions are not automatically just there but that they are the result of an evolving process shaped by policy activities and entrepreneurial behaviour responding to new challenges. Clusters as social technologies are co-evolving with new physical technologies and are therefore in constant need to change themselves. They can be regarded as an answer to the problems of achieving agreement and coordination in a context where there is a collective interest. They combine different additional elements that are important for regional development and economic growth.
Keywords: 330